2020
DOI: 10.1002/oby.22829
|View full text |Cite
|
Sign up to set email alerts
|

Intermittent Fasting and Metabolic Health: From Religious Fast to Time‐Restricted Feeding

Abstract: Over the past 10 to 15 years, intermittent fasting has emerged as an unconventional approach to reduce body weight and improve metabolic health beyond simple calorie restriction. In this review, we summarize findings related to Ramadan and Sunnah fasting. We then discuss the role of caloric restriction not only as an intervention for weight control, but importantly, as a strategy for healthy aging and longevity. Finally, we review the four most common intermittent fasting (IF) strategies used to date for weigh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
62
1
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(77 citation statements)
references
References 123 publications
2
62
1
5
Order By: Relevance
“…Whether these differences in free-living appetite and eating behaviours between IER and CER contributed to the lower adherence and to the greater number of participants not achieving our per protocol criterion of ≥5% WL within 12 weeks is unclear. Therefore, these results should be confirmed in larger samples, and further research is required to phenotype individuals who successfully lose weight with IER strategies in order to personalise dietary prescriptions to improve WL, as recently highlighted by Hoddy et al [21].…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…Whether these differences in free-living appetite and eating behaviours between IER and CER contributed to the lower adherence and to the greater number of participants not achieving our per protocol criterion of ≥5% WL within 12 weeks is unclear. Therefore, these results should be confirmed in larger samples, and further research is required to phenotype individuals who successfully lose weight with IER strategies in order to personalise dietary prescriptions to improve WL, as recently highlighted by Hoddy et al [21].…”
Section: Discussionmentioning
confidence: 72%
“…A week-by-day interaction (p=0.005) revealed that feed day EI was greater at week 2 than final week (MΔ=295 [81, 509] kcal, p=0.004), but neither differed from baseline (p≥0.245). Free-living daily hunger (Figure 2B) did not differ between measures weeks (p=0.679), but was greater on fast days relative to feed days (MΔ=15[10,21] mm, p<0.001). A week-by-day interaction…”
mentioning
confidence: 92%
“…With an increasing prevalence of obesity comes a heightened risk for the development of chronic health sequelae, including metabolic diseases, cardiovascular diseases, diabetes and cancer (Haslam & James, 2005;Withrow & Alter, 2011). Most weight-loss diet regimens, such as caloric restriction (CR), rely on limiting daily food intake, whereas time-restricted feeding and intermittent fasting (IF) limit the timing or duration of food availability (Hoddy et al, 2020). A common challenge with diet-induced weight loss is that the reduced weight is © 2021 The Authors.…”
Section: Introductionmentioning
confidence: 99%
“…A recent review of intermittent fasting protocols such as 5:2, alternate day fasting and time-restricted eating found that although weight loss can occur due to energy restriction, cardiometabolic health benefits such as increased insulin sensitivity can occur independent of weight loss. 17 Carbohydrate restriction has also been associated with reduced blood pressure in primary care patients. 11 15 Rather than hypertension being addressed by weight loss per se, it has been speculated that dietary changes may be responsible, 18 and there is evidence that hyperinsulinaemia increases sodium retention in people with T2D and hyperglycaemia.…”
Section: Introductionmentioning
confidence: 99%
“…A recent review of intermittent fasting protocols such as 5:2, alternate day fasting and time-restricted eating found that although weight loss can occur due to energy restriction, cardiometabolic health benefits such as increased insulin sensitivity can occur independent of weight loss. 17 …”
Section: Introductionmentioning
confidence: 99%